An Analysis of the Teaching Methodology Used for the Teaching of English in an Indonesian Senior High School - Muhammad Junaidi Marzuki (Universitas Islam Negeri (UIN) Mataram, 2018)
The intent of this article is to analyze a theory that informs teacher’s classroom practice in daily basis. It also addresses strengths and weakness underlying teaching approach deployed, and provides areas that need improvement for more fun, engaging and meaningful learning experience. To achieve this goal, a single observed and implemented lesson planning on Science & Technology is used, in which the analysis and evaluation is based on. It is hoped that it will increase teachers’ awareness of pedagogical approach, as well as teaching strategies used in their day-to-day teaching practice.